Gene expression and epigenetic aberrations in F1‐placentas fathered by obese males. Issue 4 (3rd March 2017) - Mitchell, Megan; Strick, Reiner; Strissel, Pamela L.; Dittrich, Ralf; McPherson, Nicole O.; Lane, Michelle; Pliushch, Galyna; Potabattula, Ramya; Haaf, Thomas; El Hajj, Nady
Abstract : Gene expression and/or epigenetic deregulation may have consequences for sperm and blastocysts, as well as for the placenta, together potentially contributing to problems observed in offspring. We previously demonstrated specific perturbations of fertilization, blastocyst formation, implantation, as well as aberrant glucose metabolism and adiposity in offspring using a mouse model of paternal obesity. The current investigation analyzed gene expression and methylation of specific CpG residues in F1 placentas of pregnancies fathered by obese and normal‐weight male mice, using real‐time PCR and bisulfite pyrosequencing. Our aim was to determine if paternal obesity deregulated placental gene expression and DNA methylation when compared to normal‐weight males. Gene methylation of sperm DNA was analyzed and compared to placentas to address epigenetic transmission. Of the 10 paternally expressed genes ( Peg s), 11 genes important for development and transport of nutrients, and the long‐terminal repeat Intracisternal A particle ( IAP ) elements, derived from a member of the class II endogenous retroviral gene family, we observed a significant effect of paternal diet‐induced obesity on deregulated expression of Peg3, Peg9, Peg10, and the nutrient transporter gene Slc38a2, and aberrant DNA methylation of the Peg9 promoter in F1 placental tissue. Epigenetic changes in Peg9 were also found in sperm from obese fathers. We therefore propose that paternal obesity renders changes in gene expression and/or methylation throughout the placental genome, which could contribute to the reproductive problems related to fertility and to the metabolic, long‐term health impact on offspring.